Biomedicine hub (S. Karger, 2016)
An interdisciplinary, peer-reviewed open access journal that aims to bring together high quality basic, translational and clinical research as well as public global health issues across biomedical fields to focus on interdisciplinary work at the forefront of medicine.
Keywords: biomedicínský výzkum; Interdisciplinary Communication; mezioborová komunikace; Public Health; věda a výzkum; veřejné zdravotnictví; Biomedical Research; lékařství